Repetitive process based design of PD-type iterative learning control laws for batch processes with time-delays - Maniarski, Robert; Paszke, Wojciech (1975- ); Rogers, Eric; Tao, Hongfeng
This paper uses linear matrix inequality techniques and the Kalman-Yakubovich- Popov lemma to design an iterative learning control law for a class of batch processes with state delays. The design procedure is based on the stability theory for repetitive processes, a class of 2D systems. A numerical example illustrates the new design and demonstrates that the design has advantages compared to the existing alternatives.
Keywords: batch processes; iterative learning control; linear matrix inequalities; repetitive processes; systems with delays